(untitled) (Proceedings of International Educators Conference, 2023)
The article discusses the use of artificial intelligence technology in legal activities. In order to introduce artificial intelligence into legal practice, it is necessary to pay serious attention to the issues of creating a system of moral values of lawyers.Despite the fact that many projects based on artificial intelligence systems, which are successfully used in legal practice, are being used in practice, it is emphasized that the most optimal solution is to ensure the mutual harmony of legal personnel and artificial intelligence.The article analyzes the problems of creating a set of data necessary for training neural networks intended for use in legal practice, examples of the use of artificial intelligence systems in national and foreign legal practice.It is possible to consider the use of artificial intelligence as a separate type of legal technology.